2021
DOI: 10.1007/s11060-021-03904-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following awake surgery depends on ability of executive function, verbal fluency, and movement

Abstract: IntroductionThe outcome of awake surgery has been evaluated based on functional factors, return to work, and oncological aspects, and there have been no reports directly examining QOL. This study aimed to investigate the outcome of QOL following awake surgery and to determine the functional factors influencing QOL. Methods Seventy patients with WHO grade II/III gliomas were included. For the assessment of QOL, we used the SF-36 and calculated summary and sub-component scores. Three summary component scores, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(68 reference statements)
1
5
0
1
Order By: Relevance
“…This initial recovery period is often characterized by sick leave for most patients and particularly in case of adjunct oncological treatments. However, at 1 year postoperatively, approximately 70% had returned to work, which was fairly similar to previous reports (50-80%) [17,20,33,37], although very high rates (near 100%) have been reported in some series [22]. Interestingly, a greater deterioration in attention and processing speed (coding) at 3 months was associated with a lower rate of return to work again within 1 year in our study.…”
Section: Cognition and Health-related Quality Of Life-is There A Conn...supporting
confidence: 91%
See 2 more Smart Citations
“…This initial recovery period is often characterized by sick leave for most patients and particularly in case of adjunct oncological treatments. However, at 1 year postoperatively, approximately 70% had returned to work, which was fairly similar to previous reports (50-80%) [17,20,33,37], although very high rates (near 100%) have been reported in some series [22]. Interestingly, a greater deterioration in attention and processing speed (coding) at 3 months was associated with a lower rate of return to work again within 1 year in our study.…”
Section: Cognition and Health-related Quality Of Life-is There A Conn...supporting
confidence: 91%
“…It could be that a reduced attention span predisposes for a more optimistic appreciation of HRQoL or that this association was merely a statistical fluke. Interestingly, Nakajima and colleagues found that a deterioration in executive function was associated with lower GH, whereas lower postoperative verbal fluency correlated with lower RP and RE at 6 months postoperatively [ 20 ]. However, they used a different cognitive test battery, the follow-up was slightly later at 6 months postoperatively, and they evaluated HRQoL at 6 months rather than the dynamics between the pre- and postoperative state, which could explain the different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relacionado con los procesos que llevan a cabo las estrategias adecuadas para la búsqueda de información y su respuesta apropiada en el menor tiempo posible (Nakajima et al, 2022). Se trabaja mediante la capacidad de improvisar verbalmente dentro de unas estructuras determinadas facilitadas por el docente.…”
Section: Fluencia Verbalunclassified
“…A sensitive and quick test that is widely used in both clinical care and research is verbal fluency. The clinical relevance of this efficient test is underlined by the fact that verbal fluency performance is also related to quality of life (Nakajima et al., 2022). In verbal fluency, participants are asked to generate as many unique words as possible within a given semantic category such as animals and professions (semantic or category fluency) or starting with a given letter (phonemic or letter fluency) within a limited time span.…”
Section: Introductionmentioning
confidence: 99%